2016
DOI: 10.1055/s-0036-1592414
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Related Changes of Amino Acid and Acylcarnitine Concentrations: The Impact of Obesity

Abstract: Objective Our primary objective was to assess the difference in amino and fatty acid biomarkers throughout pregnancy in women with and without obesity. Interactions between biomarkers and obesity status for associations with maternal and fetal metabolic measures were secondarily analyzed. Methods Overall 39 women (15 cases, 24 controls) were enrolled in this study during their 15- to 20-weeks' visit at the University of Iowa Hospitals and Clinics. We analyzed 32 amino acid and acylcarnitine concentrations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…However, there were no changes in branched chain amino acids between lean and obese women. 58 At term there was a decrease in amino acid concentrations and fetal-maternal amino acid gradients in obese women who had small for gestational age neonates compared with normal or obese women with average for gestational age neonates. 59 The decreased fetal-maternal amino acid gradients seen in some obese women may be related to altered placental amino acid transporter activity 41 and decreased placental SNAT activity.…”
Section: Differences In Maternal Metabolism In Obese and Normal Weighmentioning
confidence: 87%
“…However, there were no changes in branched chain amino acids between lean and obese women. 58 At term there was a decrease in amino acid concentrations and fetal-maternal amino acid gradients in obese women who had small for gestational age neonates compared with normal or obese women with average for gestational age neonates. 59 The decreased fetal-maternal amino acid gradients seen in some obese women may be related to altered placental amino acid transporter activity 41 and decreased placental SNAT activity.…”
Section: Differences In Maternal Metabolism In Obese and Normal Weighmentioning
confidence: 87%
“…Although these metabolite differences were not statistically significant in single metabolite analyses, this metabolic profile was significantly different during early versus mid-pregnancy. In previous studies, some of these metabolites have been linked to insulin resistance, pregnancy, or both [23][24][25][26][27][28][29][30][31]. Previous studies have observed relative decreases in fatty acids post-OGTT among pregnant women [19,20], but this is the first study to measure metabolites during both early and mid-pregnancy.…”
Section: Changes In Metabolites During An Ogtt At Early Versus Mid-prmentioning
confidence: 87%
“…Therefore, these metabolites that displayed suggestive differences in response to an OGTT warrant further investigation in larger studies. Studies suggest that acyl carnitines are tightly regulated, decrease in women during pregnancy [26,27], and have been associated with maternal and child overweight and obesity [28]. Docosapentaenoate (DPA), a fatty acid, has been inversely correlated with insulin resistance markers, and circulating levels tend to decrease during pregnancy [29].…”
Section: Changes In Metabolites During An Ogtt At Early Versus Mid-prmentioning
confidence: 99%
“…However, continuous longitudinal changes of multiple classes of plasma metabolites over pregnancy have not been described. Three recent studies described longitudinal changes in targeted maternal plasma metabolomics (including amino acids, fatty acids, and acylcarnitines) over healthy pregnancy, but each collected samples at the same fixed times in all participants, leaving gaps in the remaining weeks of pregnancy and precluding description of continuous changes over time [ 8 , 9 , 10 ]. A few additional preliminary studies have measured metabolites (amino acids, fatty acids, and others) in maternal plasma at multiple points in pregnancy, but were all limited by methodological challenges including a small sample size (30 or fewer participants at each time point) and lack of repeated measurements on the same women [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, changes in metabolite concentration may be affected by maternal and fetal factors. For example, a number of studies (nearly all cross-sectional) have shown that maternal plasma metabolites (non-esterified fatty acids, branched chain amino acids, and some acylcarnitines, among others) differ by pre-pregnancy body mass index (BMI) [ 9 , 15 , 16 , 17 , 18 , 19 ]. Fetal sex may affect metabolites in maternal plasma or amniotic fluid [ 20 , 21 ], and one study in healthy pregnancy reported subtle differences in metabolomic profile by Hispanic ethnicity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%